CATASTROPHIC SHIFT OF OBESITY IN THREE ZONES OF SUB-HIMALAYAN REGION, INDIA, AND ITS CORELATION WITH THE DIETARY INTAKE - Thapliyal, Vinita; Singh, Karuna; Joshi, Anil (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective is to study the prevalence of obesity and overweight in three zones of sub-Himalayan Region and its corelation with the dietary intake. Methods: A survey was conducted in three zones of Uttrakhand (Dehradun, Rudraprayag, and Uttarkashi), India, representing the urban, semi-urban, and rural village population (18â€“45 years) of the state. For the study, 100 adults were selected from each of the 3 zones, respectively, to make a total sample size of 300 adults using purposive random sampling. Results: The high prevalence obesity and overweight occur among urban zone (Dehradun), followed by semi-urban zone, Rudraprayag, district of Uttrakhand. In Dehradun, 6.1% of males and 29.4% of females were obese, whereas 62.1% males and 58.8% of females were overweight. In Rudraprayag, 13.6% of males and 14.6% of females were obese, whereas 35.6% of males and 39% of females were overweight. In rural zone (Uttarkashi), there were no cases of obesity among both males and females. Conclusion: A high prevalence rate of obesity was depicted in the urban zone of Uttrakhand region. Urbanization seems to have a positive significant impact on the prevalence of obesity with women being at greater risk.